Analisis Strategi Pengembangan Usaha Syariah Batu Bata dalam Meningkatkan Pendapatan (Studi Kasus Usaha Batu Bata Milik Bapak Ajmalul Amri di Korong Palak Atok Kecamatan Lubuk Alung Kabupaten Padang Pariaman) - Rabiatul Adawiyah; Rika Widianita (Lembaga Yasin AlSys, 2026)
The development of micro, small, and medium enterprises (MSMEs), particularly in the brick production sector, has become a focus in various previous studies. However, research that specifically discusses sharia-based business development strategies using a SWOT analysis approach in brick-making businesses at the local level remains limited. This study aims to analyze sharia business development strategies in increasing income in the brick-making business owned by Ajmalul Amri in Korong Palak Atok, Lubuk Alung Subdistrict, Padang Pariaman Regency. This study employed a qualitative approach with a case study design. The main and supporting informants were selected through the purposive sampling technique. Data were collected through in-depth interviews, observation, and documentation and were then analyzed using qualitative descriptive techniques with a SWOT approach (Strengths, Weaknesses, Opportunities, Threats). The results show that the business is in a defensive strategy position, with weak internal conditions indicated by limited capital, simple production technology, and dependence on weather factors that cause fluctuations in production and income. On the other hand, market opportunities remain open, but the business faces the threat of high competition. These findings contribute to the development of studies on strategic management and Islamic economics in the context of traditional-based microenterprises and broaden understanding of the importance of integrating internal and external analysis in formulating business strategies. The conclusion of the study emphasizes that strengthening the internal factors of the business is the main strategy for increasing business sustainability and income. The practical implication is that business actors and stakeholders need to strengthen access to capital, production efficiency, and adaptive business management to support the development of sharia-based microenterprises.